2017
DOI: 10.1002/icd.2040
|View full text |Cite
|
Sign up to set email alerts
|

“I'm an ogre so I'm very hungry!” “I'm assistant ogre”: The Social Function of Sibling Imitation in Early Childhood

Abstract: Siblings' imitative behaviors were investigated in 39 middle‐class dyads during six 90‐min home sessions at both Time 1 (M age: older sibling = 4.4 years; younger sibling = 2.4 years) and Time 2 (2 years later). Although younger siblings imitated most often at T1 and T2, older siblings' imitation increased proportionally over time in comparison to younger siblings. Findings highlight the affiliative nature of imitation that occurred during reciprocal play interactions, via positive responses, and the content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…In terms of humorous categories, younger compared to older sibling dyads produced more sound play, such as overexaggerated singing. ‘Silly’ rhyming and overexaggerated tones of voice are commonly observed with preschool‐aged friends and siblings (Howe et al ., ). According to Garvey (), as soon as children learn a new rule or convention, they have fun distorting and exaggerating it.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In terms of humorous categories, younger compared to older sibling dyads produced more sound play, such as overexaggerated singing. ‘Silly’ rhyming and overexaggerated tones of voice are commonly observed with preschool‐aged friends and siblings (Howe et al ., ). According to Garvey (), as soon as children learn a new rule or convention, they have fun distorting and exaggerating it.…”
Section: Discussionmentioning
confidence: 97%
“…Given that children's responses to humour may differ according to features of the sibling relationship, we coded children's responses to humour using a scheme adapted for coding children's responses to sibling imitation during free play (Howe, Rosciszewksa, & Persram, ). Children's responses to humour included (1) no response ; (2) positive/neutral ; (3) negative ; (4) clarification ; (5) imitation ; and (6) extension (see Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains unclear how one sibling influences the other and whether this influence is socially or cognitively driven. Although some researchers have found that older siblings facilitate ToM development (e.g., Hughes & Ensor, ), it is also evident that younger children learn verbal content through imitating their older siblings (Howe, Rosciszewska, & Persram, ). Similarly, lie‐telling is achieved using both cognitive (e.g., Evans & Lee, ; Evans et al, ; Leduc, Williams, Gomez‐Garibello, & Talwar, ; Talwar & Lee, ; Williams et al, ) and social means (Talwar & Crossman, ; Talwar, Lavoie, Gomez‐Garibello, & Crossman, ; Talwar & Lee, ; Warr, ; Wilson, Smith, & Ross, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the two first years of life, children gradually increase their imitative behaviors both in frequency and complexity, along with the development of their cognitive and social abilities (Vivanti & Hamilton, 2014). Children imitate their siblings, peers and parents at every moment to learn new abilities (Howe et al, 2018; Zmyj & Seehagen, 2013). Imitation is an essential lever for learning of new motor skills (Pfeifer et al, 2008), and cognitive skills (Hurley & Chater, 2005; Strid et al, 2006; Vivanti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%